On the amplification role of collateral constraints - Caterina Mendicino (Bank of Canada, 2008)
Following the seminal contribution of Kiyotaki and Moore (1997), the role of collateral constraints for business cycle fluctuations has been highlighted by several authors and collateralized debt is becoming a popular feature of business cycle models. In contrast, Kocherlakota (2000) and Cordoba and Ripoll (2004) demonstrate that collateral constraints per se are unable to propagate and amplify exogenous shocks, unless unorthodox assumptions on preferences and production technologies are made. The aim of this paper is to examine the contribution of costly debt enforcement procedures in the amplification of business cycle fluctuations through collateral constraints. We show that for realistic degrees of inefficiency, collateral constraints can significantly amplify the effects of productivity shocks on output even under standard assumptions on preferences and technology.
Keywords: E20; E3; E32; 330; Business fluctuations and cycles; Credit and credit aggregates; Kapitalbedarf; Kreditsicherung; Produktivität; Schock; Konjunktur; Theorie